Comparison of Student Learning Outcomes with PBL and CTL Models - Budi Setiawan; Hamka Lodang; Muhammad Wiharto (Magister Pendidikan Biologi, Universitas Negeri Medan, 2023)
The lack of student learning outcomes is caused by the learning model that is usually taught by teachers tends to be monotonous, therefore this research was conducted as an alternative for teachers in implementing an effective model. This study was a quasi experiment research which purposed to know the differences of student learning outcomes on concept environment changes who taught by problem based learning and contextual teaching and learning at grade X student SMA Negeri 8 Pinrang. The population of this study was whole grade X students of SMA Negeri 8 Pinrang as many as eight classes and the sample was X MIPA 1 class as experiment group I and X MIPA 2 class as experiment group II where each group consist of 30 students. The data was got by givent pretest and posttest. The descriptive statistic analysis showed the average grade of experiment group I was 0,587 with categorized medium and the average grade of experiment group II was 0,402 with categorized medium. The grades showed that student who were thought by problem based learning was better in comparasion than the student who were though with model contextual teaching and learning. The inferensial statistical analysis result through t-test showed sig. (2-tailed) score as 0,000 which less than α (0,05) so that, the researcher make conclucion like there is the differences of students learning outcomes on concept of environment changes who taught by problem based learning with contextual teaching and learning at grade X students of SMA Negeri 8 Pinrang.